Global production networks and resources in WA - Rainnie, Alistair; Fitzgerald, Scott; Ellem, Bradon (Springer, 2014)
This chapter draws on the literature on global networks and spatiality to examine the development of Western Australia and its relationship with the resource sector, with an emphasis on institutional capture, the dynamics of regional development dominated by large external capital, and a contested notion of place.